Strategy for Institution Building for Management of Common Lands: Steps Taken in the Aravalli Hills of Haryana - Rawat, J. K. (Indian Forester, 1998)
Absence of effective institutions in the villages result in mismanagement of common property resources. Haryana Forest Department , in its Aravalli Project , is trying to develop institutions in the project villages for sustainable management of rehabilitated common lands by the village communities in the future. This paper describes the strategy adopted and steps taken for this purpose.